Short-term pharmacological suppression of the hyperprolactinemia of infertile hCG-overproducing female mice persistently restores their fertility - Ratner, Laura Daniela (2012)
Female infertility is often associated with deregulation of hormonal networks, and hyperprolactinemia is one of the most common endocrine disorders of the hypothalamic-pituitary axis affecting the reproductive functions. We have shown previously that transgenic female mice overexpressing human chorionic gonadotropin β-subunit (hCGβ+ mice), and producing elevated levels of bioactive LH/hCG, exhibit increased production of testosterone and progesterone, are overweight and infertile, and develop hyperprolactinemia associated with pituitary lactotrope adenomas in adult age. In the present study, we analyzed the influence of the hyperprolactinemia of hCGβ+ females on their reproductive phenotype by treating them with the dopamine agonists, bromocriptine and cabergoline. Long-term bromocriptine treatment of adult mice was effective in the control of obesity, pituitary growth, and disturbances in the hormone profile, demonstrating that hyperprolactinemia was the main cause of the hCGβ+ female phenotype. Interestingly, short-term treatment (1 wk) with cabergoline applied on 5-wk-old mice corrected hyperprolactinemia, hyperandrogenism, and hyperprogesteronemia, prevented pituitary overgrowth, normalized gonadal function, and recovered fertility of adulth CGβ+ females after hormone-induced and natural ovulation. The same cabergoline treatment in the short term applied on 3-month-old hCGβ+females failed to recover their reproductive function. Hence, we demonstrated that the short-term cabergoline treatment applied at a critical early stage of the phenotype progression effectively prevented the hyperprolactinemia-associated reproductive dysfunction of hCG-overproducing females. Copyright © 2012 by The Endocrine Society.